The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s10659-020-09789-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective Resonant Model and Simulations in the Time-Domain of Wave Scattering from a Periodic Row of Highly-Contrasted Inclusions

Abstract: The time-domain propagation of scalar waves across a periodic row of inclusions is considered in 2D. As the typical wavelength within the background medium is assumed to be much larger than the spacing between inclusions and the row width, the physical configuration considered is in the low-frequency homogenization regime. Furthermore, a high contrast between one of the constitutive moduli of the inclusions and of the background medium is also assumed. So the wavelength within the inclusions is of the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…The case of highly contrasted inclusions able to produce internal, low-frequency, resonances is more challenging. Already considered in the scalar, antiplane, case by Pham et al [26] and Touboul et al [27], it is difficult to anticipate how the effect of these resonances translates in two-or three-dimensional elasticity. From a practical point of view, the study of guided waves by such imperfect interfaces and their link with Rayleigh, Stoneley and Love waves in realistic configurations is of interest in a geophysical context.…”
Section: Discussionmentioning
confidence: 99%
“…The case of highly contrasted inclusions able to produce internal, low-frequency, resonances is more challenging. Already considered in the scalar, antiplane, case by Pham et al [26] and Touboul et al [27], it is difficult to anticipate how the effect of these resonances translates in two-or three-dimensional elasticity. From a practical point of view, the study of guided waves by such imperfect interfaces and their link with Rayleigh, Stoneley and Love waves in realistic configurations is of interest in a geophysical context.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of resonant meta-interfaces, an alternative approach was to obtain effective jump conditions by applying a suitable homogenization process [33,34]. Moreover, some studies on elastic wave propagation showed that when the interphase is located between two surrounding media with microstructure, inertial properties also play a pivotal role in the modeling of the equivalent interface [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In elasticity, works on interface homogenization focused first on rows of non-resonant inclusions [9,28,8,27], and then on resonant inclusions [31,29,41]. In [31,41], two-scale asymptotic method has been combined with matched-asymptotic expansions to yield effective jump conditions, both in the frequency domain [31] and in the time domain [41]; in the latter case, the jump conditions turn out to be non-local. Second-order accuracy in terms of the small ratio k m h has been reached, where k m is the wavenumber in the background medium and h is the typical size of the inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…As is usual in structural dynamics, a phenomenological model is therefore considered. In this framework, the results presented in [41,40] are modified and need to be re-examined on their main features: (i) effective jump conditions, (ii) energy balance, (iii) auxiliary fields, and (iv) discretization of the interfaces. These four points are addressed here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation